Design impact of 6.08 kWp grid-connected photovoltaic system at Malaysia green technology corporation / Mohamad Zhafran Hussin ...[et al.] - Hussin, Mohamad Zhafran; Omar, Ahmad Maliki; Md Zain, Zainazlan; Shaari, Sulaiman; Zainudddin, Hedzlin (UiTM Press, 2012)
System design issues of a GridConnected Photovoltaic (GCPV) system installed in Malaysia Green Technology Corporation (MGTC), Malaysia based on field condition under Malaysia’s climate is presented in this paper. Several important factors related with design procedure which affect the GCPV system performances are identified to be solar irradiance, temperature, de-rating factor and wind speed. System design’s sizing and natural environmental analysis are two common issues and considered to be among the most crucial part of the study with the objective of enhancing the GCPV system performance in Malaysia’s perspective. The power output is being determined by the sizing of the GCPV system. In addition, by connecting a none appropriate numbers of serial modules per string will give a non-optimum system design. Hence, the inverter performance is affected. The analysis fully utilizes the in-field data as a guide for sizing PV array and inverter, with the aim of guiding the designer during initial design stage for Malaysia’s climate.